Guest

If x = r cos a cosb cos c, y = cosa cosb sinc, z = r sina cosb u = r sinb then x square + y square + z square + u square =

If x = r cos a cosb cos c, y = cosa cosb sinc, z = r sina cosb  u = r sinb then x square + y square + z square + u square =

Grade:11

1 Answers

Yash Baheti IIT Roorkee
askIITians Faculty 97 Points
8 years ago
Hi,

Follow the following steps :

Substitute the values in the expression. Observe the first term and second term carefully. If you take whatever common than this will be COMBINED one term.
Than this term will be combined with the third term and similarly with fouths term. The final answer will be r^2.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free